Dietary habits and weight change during the second wave of the COVID-19 pandemic among the Egyptian population - Samar Abd ElHafeez; Yasmine Amr Issa; Samar Tharwat; Ahmed Yahia Elmowafy; Karem Mohamed Salem; Noha Gaber Amin; Mohammed Kamal Nassar; Ramy Ghazy Mohamed (BMC Nutrition)
Abstract Background The pandemic of coronavirus disease–19 (COVID-19) has a profound influence on the health of the population. This study aimed to assess the weight changes and its relation to the dietary habits and physical activity among adult Egyptian population during the second wave of COVID-19 pandemic. Materials and methods This cross–sectional study was conducted using anonymous online questionnaire. The questionnaire was distributed across Egypt via community–based networks, social and institutional emailing lists, and professional organizations to collect data on sociodemographic, clinical history, dietary and lifestyle habits, physical activity, anthropometric measurements, and stressing factors. Results The study participants (n = 1000) had a median (interquartile range) age of 34.0 (23.0–40.0) years, with 18.7% males, 96.6% having university or postgraduate education. Among them, 69.1% reported weight gain, 21.3% no change, and 9.6% weight loss. Weight loss was predicted by following COVID-19 pandemic reports daily [adjusted odds ratio (AOR) = 0.50 (95% CI, 0.27–0.93), p = 0.03], monthly income change [AOR = 2.52 (95% CI, 1.51–4.22), p < 0.001], starting antidepressants [AOR = 3.57 (95% CI, 1.08–11.76), p = 0.03], and increase in social media use [AOR = 1.81 (95% CI, 1.05–3.13), p = 0.03]. Weight gain was predicted by starting a diet during the second wave of COVID-19 pandemic [AOR = 1.57 (95% CI, 1.11–2.21), p = 0.01], physical activity during the second wave of COVID-19 pandemic [AOR = 0.49 (95% CI, 0.35–0.69), p < 0.001], and unhealthy food intake [AOR = 0.40 (95% CI, 0.28–0.57), p < 0.001] Conclusions More intervention programs aiming to improve dietary habits and increase physical activity should be rapidly implemented to reduce the consequences of the pandemic on the Egyptians to keep healthy weight.